Emerging Practices In Community Development Agreements - Loutit, Jennifer; Mandelbaum, Jacqueline; Szoke-Burke, Sam (Journal of Sustainable Development Law and Policy, 2025)
Community Development Agreements (CDAs) have the potential to facilitate the delivery of tangible benefits from large-scale investment projects, such as mines or forestry concessions, to affected persons and communities. To be effective, however, CDAs must be adapted to the local context, meaning that no single model agreement or process will be appropriate in every situation. Nonetheless, leading practices are emerging which can be required by governments, voluntarily adopted by companies, and demanded by communities. These practices are grounded in ensuring that all parties are sufficiently informed, capacitated, and prepared to engage in meaningful negotiations regarding how the investor’s operations should benefit local stakeholders. This article reviews existing research on CDAs, as well as available agreements from the extractive sector in Australia, Canada, Laos, Papua New Guinea, Ghana and Greenland. It articulates seven broad leading practices and how different stakeholders could work to achieve more effective agreements.